Immunoglobulin genes, reproductive isolation and vertebrate speciation. Issue 7 (4th July 2022) - Collins, Andrew M; Watson, Corey T; Breden, Felix
Abstract: Reproductive isolation drives the formation of new species, and many genes contribute to this through Dobzhansky–Muller incompatibilities (DMIs). These incompatibilities occur when gene divergence affects loci encoding interacting products such as receptors and their ligands. We suggest here that the nature of vertebrate immunoglobulin (IG) genes must make them prone to DMIs. The genes of these complex loci form functional genes through the process of recombination, giving rise to a repertoire of heterodimeric receptors of incredible diversity. This repertoire, within individuals and within species, must defend against pathogens but must also avoid pathogenic self‐reactivity. We suggest that this avoidance of autoimmunity is only achieved through a coordination of evolution between heavy‐ and light‐chain genes, and between these genes and the rest of the genome. Without coordinated evolution, the hybrid offspring of two diverging populations will carry a heavy burden of DMIs, resulting in a loss of fitness. Critical incompatibilities could manifest as incompatibilities between a mother and her divergent offspring. During fetal development, biochemical differences between the parents of hybrid offspring could make their offspring a target of the maternal immune system. This hypothesis was conceived in the light of recent insights into the population genetics of IG genes. This has suggested that antibody genes are probably as susceptible to evolutionary forces as other parts of the genome. Further repertoire studies in human and nonhuman species should now help determine whether antibody genes have been part of the evolutionary forces that drive the development of species. Abstract : Coordinated evolution is required to avoid incompatibilities between interacting genes, and the genetics of immunoglobulins (IGs) may make them especially prone to such incompatibilities. We argue here that the hybrid offspring of two diverging populations will carry a heavy burden of incompatibilities, resulting in a loss of fitness. IG genes may therefore be critical to the processes that lead to reproductive isolation and the development of new species.